FRACTAL PROPERTIES OF MICROPLASMA BREAKDOWN AND STRUCTURAL HETEROGENEITY OF SEMICONDUCTOR MATERIALS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
This work presents experimental results on the study of current-voltage characteristics and oscillograms of microplasma pulses of the p-n-junction avalanche breakdown. Based on the latter, the pulse duration distributions are determined. As a result, it is shown that microplasma noise has fractal properties. The latter form the basis of avalanche breakdown types developed classification. The correlation between the fractal dimension of microplasma noise and structural inhomogeneities of functional semiconductor structures is revealed.